KEGIATAN LITERASI 15 MENIT TERHADAP MINAT BACA KELAS IV SD NEGERI SALATIGA 05 - Alfa Reza Silvia Putri (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
THE 15 MINUTE LITERATION ACTIVITIES AGAINST READING INTEREST OF 4TH GRADERS SD NEGERI SALATIGA 05This research aims to find out the reading interest of 4th graders SD Negeri Salatiga 05 after 15 minutes of literacy activity. This research is used qualitativ descriptive approach. The subject of this research is 4th graders students of SD Negeri Salatiga 05. Data collection was done using observation and questionnaire methods. The result of this research found several students who experienced an increase in reading interest after literacy activities were conducted, but there are still students who have low reading interest. The low interest in reading students is due to lack of attention and motivation towards books and the lack of the role of the teacher. The role of the teacher is very important, this teacher must understand the characteristics of each student's characteristics. Reading interest is felt to be very important because reading is an important part of growing character and competitive capital in the 21st century. This 15-minute literacy activity is one of the government's efforts to increase students' interest in reading in Indonesia to create a culture of literacy in formal education.